Mastering macromedia director 6 - Henderson, Chuck (SYBEX, 1997)
This is your best source for a thorough understanding of how Director 6 really works. From casts and scripts to Lingo and Shockwave, get expert advice on building interactive content for CD-ROMs, intranets, and the Web. A detailed catalog of the latest Xtras and Xobjects helps expand the power of Director, while an extensive, annotated Lingo command reference gets the information you need, fast. The CD features shareware Xtras, sample Director movies, tutorial files, and save-disabled versions of several Macromedia products